Digital Technology Integration in Kerinci Arabica Coffee Ethnoscience: Students' Responses - Indah Kencanawati Djazi; Ramadani Ramadani; Titin Mairisiska; Lince Meriko; Fakhri Ramadhan (Universitas Syiah Kuala, 2026)
This study investigated the ethnoscience dimensions embedded in Kerinci Arabica coffee processing and explored students' responses to integrating digital technology into contextual science education. Rather than adopting a mixed-methods design, this study applied qualitative and quantitative approaches independently to address different research objectives. The qualitative approach was used to identify ethnoscience dimensions, whereas the quantitative approach was employed to explore students' responses toward digital technology integration in contextual science education. Qualitative data were obtained through observations, semi structured interviews, and documentation involving five Arabica coffee farmers and processors in Kerinci. Quantitative data were collected from questionnaires distributed to 35 fourth-semester students of the Science Education Program at IAIN Kerinci. Data were analyzed using interactive qualitative analysis, descriptive statistics, and triangulation. The results showed that the processing of Kerinci Arabica coffee reflects local genius integrating cultural values, experiential knowledge, and scientific concepts in biology, chemistry, physics, and food technology. Processing stages, including harvesting, pulping, sorting, drying, roasting, resting, grinding, and packaging, demonstrated strong potential as contextual science learning resources. Questionnaire findings indicated that students responded positively to the integration of digital technology through multimedia learning, interactive platforms, digital curriculum systems, and project-based assessment. Students perceived that these learning approaches supported their conceptual understanding and promoted active engagement in contextual science learning. Quantitative findings demonstrated that all indicators achieved scores above 85% and were classified as very good, with the media aspect receiving the highest evaluation. These findings indicate that digital technology integration supports the development of innovative, contextual, and ethnoscience-based science education